MOTHERS POSITIVE TO CRYPTOSPORIDIUM PARVUM AS A RISK FACTOR FOR THE PRESENCE OF THE PATHOGEN IN NEWBORN ALPACAS WITH DIARRHEA - Aguilar J., R Vladimir (2013)
The aim of the study was to establish whether the presence of Cryptosporidium parvum in the dam is a risk factor for the presentation of the pathogen in the baby alpaca. The study included 698 alpaca dams and their offspring less than 30 days of age. The sampling took place from January till March 2007 in the localities of La Raya, Choquecota, Chillihua, Maranganí and Silli in Canchis province, Cusco, Peru. Fecal samples were collected from the rectum, processed using the Modified Ziehl-Neelsen stain and observed by microscopy. Risk analysis was done through logistic regressions. Results showed that a baby alpaca born from a positive dam to C. parvum was 2.1 times more likely to get infected with the parasite as compared with others born from a negative dam (p<0.05). Likewise, sex and presence of diarrhea were not significant, whereas place of breeding showed to be a protection factor for newborns in peasant communities as compared to those born in experimental station farms.